2008
DOI: 10.1007/s10741-007-9077-3
|View full text |Cite
|
Sign up to set email alerts
|

Aminopeptidase A inhibitors as centrally acting antihypertensive agents

Abstract: Among the main bioactive peptides of the brain renin-angiotensin system, angiotensin (Ang) II and AngIII exhibit the same affinity for the type 1 and type 2 Ang receptors. Both peptides, injected intracerebroventricularly, cause similar increase in blood pressure (BP). Because AngII is converted in vivo to AngIII, the identity of the true effector is unknown. This review summarized recent insights into the predominant role of brain AngIII in the central control of BP underlining the fact that brain aminopeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…Ang III possesses effects and receptor-binding affinities similar to those observed for Ang II, suggesting that this heptapeptide may be equally or even more important than Ang II in some actions, e.g., aldosterone or vasopressin release (60,63). Indeed, there is a drug development that targets Ang III formation with the idea that it might be a treatment strategy for certain forms of hypertension (5,6). Our results document an abundance of Ang III formation in the medulla, providing support for a pathway by which Ang III might interact to affect aldosterone and vasopressin.…”
Section: Discussionmentioning
confidence: 99%
“…Ang III possesses effects and receptor-binding affinities similar to those observed for Ang II, suggesting that this heptapeptide may be equally or even more important than Ang II in some actions, e.g., aldosterone or vasopressin release (60,63). Indeed, there is a drug development that targets Ang III formation with the idea that it might be a treatment strategy for certain forms of hypertension (5,6). Our results document an abundance of Ang III formation in the medulla, providing support for a pathway by which Ang III might interact to affect aldosterone and vasopressin.…”
Section: Discussionmentioning
confidence: 99%
“…Ang II and Ang III have similar affinities for Ang II receptors and both peptides stimulate pressor responses by activating sympathetic nervous system activity, inhibiting the baroreflex at the level of the nucleus tractus solitarius and increasing release of arginine vasopressin into the circulation. Studies using selective APA (EC33) and aminopeptidase N (PC18) inhibitors have demonstrated that brain Ang III (not Ang II, as in the periphery) plays a predominant role in BP control in animal models and have identified APA as a potential therapeutic target for the treatment of hypertension [68][69][70][71] (Table).…”
Section: Centrally Acting Aminopeptidase Inhibitorsmentioning
confidence: 99%
“…Orally administered RB150, a dimer of EC33, has been shown to enter the brain of SHR and DOCA (deoxycorticosterone acetate)-salt rats to inhibit brain APA activity and block the formation of Ang III and to normalize BP for several hours 68,70,71 (Table). The RB150-induced depressor response was related to inhibition of arginine vasopressin release, resulting in a diuresis and reduction in volume, and a decrease in sympathetic tone, resulting in reduced vascular resistance.…”
Section: Centrally Acting Aminopeptidase Inhibitorsmentioning
confidence: 99%
“…If the 125 I-Ang II is metabolized to 125 I-Ang III, this could support the hypothesis that Ang III is the active angiotensin in the brain (Abhold and Harding, 1988;Bodineau et al, 2008).…”
mentioning
confidence: 67%
“…Thus, sarcosine 1 Ang II may better mimic Ang III than Ang II (Wright et al, 1989). This takes on great importance considering the ongoing debate regarding the main effector peptide of the brain renin-angiotensin system-Ang II versus the heptapeptide Ang III (Harding and Felix, 1987;Zini et al, 1996;Kokje et al, 2007;Bodineau et al, 2008;Speth and Karamyan, 2008). Moreover, if only Ang III can activate brain AT 1 receptors (the angiotensin III hypothesis), then Ang II either does not bind to AT 1 receptors in the brain, or it binds to the brain AT 1 receptors without causing a response (Kokje et al, 2007;Speth and Karamyan, 2008).…”
mentioning
confidence: 99%